4×4 Bit-Slice Integer Matrix Multiplier with 32-Bit Superconductor - Srinivasulu, Dr. K. (International Journal of Advanced Science and Technology, 2019)
Rapid single-flux-quantum (RSFQ) circuits are expected to be a future integrated circuits technology for its high speed and low power consumption. An 8-bit serial Microprocessor (FLUX-1), bit-serial microprocessors (CORE1 series), a bit-serial asynchronous microprocessor (SCRAM2) , and an 8-bit serial microprocessor (CORE e4) Had been deliberate in my opinion. A 32-piece 4×4 piece reduce RSFQ lattice multiplier is expert furnished. The multiplier usually contains of bit-lessen multipliers and bit-lessen adders. The duplication of unsigned whole huge variety grids is finished through manipulate alerts. The grid multiplier applied synchronous simultaneous circulate timing. The consequences show that 16-piece bit-cut coping with has minimum dormancy at 10 GHz.